Early financial education for children - Sabri, Mohamad Fazli; Ramli, Nurhayatul Nira (Universiti Putra Malaysia Press, 2019)
"If you want to see the future of a country, then look at its young men and women today- Saidina Ali R.A”. The words of Saidina Ali R.A have shown that to build a strong future generation, efforts must begin today. Similarly in the matter of managing personal finances. To produce a Malaysian society that is financially literate in the future, financial management knowledge and skills needs to be introduced to children at the earliest age. Early Financial Education for Children is a guide for parents and educators towards preparing the younger generation (children and students) to face various consumer financial challenges now and in the future. Readers are exposed to the basic concepts of financial management that · include topics such as financial objectives, wants and needs, savings and deposits, allowances and pocket money, budgets and expenses as well as credit and grants. Apart from tips and guidance, the uniqueness of this book is that it provides notes and worksheets as reinforcement for the topics discussed.